Food, Obesity Discourses and the Subjugation of Environmental Knowledge. (27th February 2015) - O'Flynn, Gabrielle; Leahy, Deana; Gray, Emily; Cutter-Mackenzie, Amy; Eames, Chris
Abstract In this article, I critically analyse how meanings of health and food, tied to obesity reduction, 'subjugate' environmental priorities and knowledges of food. To do this, I explore the meanings of health and food constructed in the NSW Health Munch & Move program. I examine the use of language to construct notions of food and health that are not only difficult to challenge, but difficult to think otherwise, including in relation to environmental perspectives of food. I argue that as calculative and individualised conceptualisations of food and health become more and more 'common sense' (Mudry, 2009), there is a 'closing off' of what is thinkable and doable in relation to food and health. The subjugation of environmental priorities of food takes place both through their marginalisation and through how we are invited to define the place of food in our lives.